Perspectives of transformations of the forms of international cooperation (on the example of G20’s activity) - Porokhovnyk, Khrystyna (Видавництво Львівської політехніки, 2013)
The article investigates the specifity of development of the modern international connections in the context of the activity of the countries – members of the Group of Twenty. The purpose of the article is identifying the patterns of development and transformation of world economy, which leaks from the activity of the countries – leaders of the world. The article appraises the retrospective review and current state of effectiveness of club’s activity; it also prognosticate the future perspectives of development in cooperation between countries of G20.
Keywords: Group of Twenty; international community; crisis; economy; finances; summit; countries – leaders; prognosis